Longitudinal outcomes of dialysis‐dependent patients undergoing isolated coronary artery bypass grafting. Issue 3 (7th February 2019) - Bianco, Valentino; Kilic, Arman; Gleason, Thomas G.; Aranda‐Michel, Edgar; Navid, Forozan; Sultan, Ibrahim
Abstract: Background: Dialysis‐dependent patients have a higher risk of short‐term morbidity and mortality following cardiac surgery. However, longitudinal survival and readmissions in this patient population after isolated coronary artery bypass grafting (CABG) are lacking in the literature. Methods: All patients undergoing isolated CABG from 2011 to 2017 were included. Perioperative data were retrospectively extracted from a prospectively maintained cardiac surgical database with a primary focus on longitudinal mortality and readmissions. Results: The total study population consisted of 6874 nondialysis‐dependent patients and 174 patients with dialysis dependence. Patients in the dialysis‐dependent group presented a higher risk of morbidity and mortality as reflected in the Society of Thoracic Surgeons‐Predicted Risk of Morbidity and Mortality (STS‐PROM) (8.4% ± 9.7% vs 2.3% ± 3.9%; P < 0.001). Operative (30‐day) mortality was significantly higher in the dialysis group (8.6% vs 2.3%; P < 0.001). Unadjusted outcomes yielded 30‐day (92% vs 98%; P < 0.001), 1‐year (80% vs 94%; P < 0.001), and 5‐year (38% vs 84%; P < 0.001) survival that was significantly worse for the dialysis group. Freedom from readmission at 30 days (93% vs 87%; P = 0.005), 1 year (78% vs 56%; P < 0.001), and 5 years (62% vs 39%; P < 0.001) was significantly better for the nondialysis cohort. Dialysis dependence was an independent predictor of mortality at 30 days (hazard ratio [HR], 3.86; 95% confidence interval [CI], 2.96, 5.03; P < 0.001), 1 year (HR, 3.20; 95% CI, 2.14, 2.79; P < 0.001), and 5 years (HR, 4.02; 95% CI, 3.07, 5.26; P < 0.001) despite risk adjustment. Conclusion: Dialysis‐dependent patients have significantly elevated operative risk, which translates to worse short‐ and long‐term survival following isolated CABG. The need for dialysis alone is an independent predictor of both mortality and readmission in the midterm.